Management of Resistant Herpetic Whitlow: A Case of Recurrent Herpetic Whitlow Resistant to Standard Therapy - Singal, Amit; Wong, Ting Ting; Lipner, Shari R. (Case reports in dermatology, 2025)
Introduction: Herpetic whitlow, due to herpes simplex virus (HSV) type 1 or 2, typically presents with vesicles that may coalesce into bullae. Herpetic whitlow often resolves without intervention but can be treated with antiviral medications. Case Presentation: Herein is a report of a 68-year-old female patient with a history of well-controlled human immunodeficiency virus (HIV) infection and a 4-year history of recurrent HSV-2 herpes genitalis who failed multiple trials of standard antiviral therapy clinically confirming a case of resistant HSV-2 infection, with recurrent tender lesions on her digits. Physical examination showed bullae involving the nail folds of her right thumb and left index finger. Initial PCR was negative for HSV-1 and HSV-2, but repeat PCR was positive for HSV-2. Treatment with foscarnet resulted in clinical improvement of both herpetic whitlow and herpes genitalis. Conclusion: Though herpetic whitlow typically resolves without intervention, a case is described of recurrent lesions in an HIV-positive patient unresponsive to multiple first-line antiviral treatment regimens and an interdisciplinary approach to treatment in a challenging case.